The role of green and digital technology convergence on carbon emission reduction: evidence from China - Hu, Jing; Sun, Qinghui; Wang, Wenjing (Frontiers in Environmental Science, 2024)
Green technology has received continuous attention and facing challenges of transformation because of the growing environmental concern, especially the carbon emissions resulting in global warming. In the Industry 4.0 era, green technology transforms into smart green technology benefits from the convergence with digital technologies. However, little research investigates the role of green and digital technology convergence (GDC) on carbon emission reduction. This study proposes a novel measurement of the GDC level of enterprise based on the network method and examines its pattern and dynamic. Moreover, we empirically analyze the impact of GDC on carbon emission reduction. Results show that GDC has a significant carbon reduction effect. Moreover, GDC reduces enterprises' carbon emissions by improving green innovation quality. Furthermore, an enterprise's technology convergence capability moderates the focal relationship. The heterogeneity analysis results reveal that the carbon reduction effect of GDC is stronger in large, state-owned, non-labor-intensive and heavypollution enterprises. The findings contribute to a better understanding of the fusion of greening and digitalization and provide useful insights for sustainable development policy-making.